2020
DOI: 10.1186/s12866-020-01918-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the vaginal microbiota associated with primary ovarian failure

Abstract: Background: Primary ovarian failure (POF) is defined as follicular failure in women of reproductive age. Although many factors are speculated to contribute to the occurrence of POF, the exact aetiology remains unclear. Moreover, alterations in the microbiome of patients with POF are poorly studied. Results: This study investigated the vaginal microbiota of 22 patients with POF and 29 healthy individuals. Highthroughput Illumina MiSeq sequencing targeting the V3-V4 region of the 16S ribosomal RNA (rRNA) gene wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
(63 reference statements)
4
14
0
Order By: Relevance
“…Early studies established the paradigm that, following menopause, vaginal Lactobacillus decreases, and overall bacterial levels and diversity are altered ( 22 ). Similar results have been observed in women with POF ( 23 , 24 ). POI, POF, early menopause, and natural menopause reflect different stages of ovarian aging.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Early studies established the paradigm that, following menopause, vaginal Lactobacillus decreases, and overall bacterial levels and diversity are altered ( 22 ). Similar results have been observed in women with POF ( 23 , 24 ). POI, POF, early menopause, and natural menopause reflect different stages of ovarian aging.…”
Section: Introductionsupporting
confidence: 89%
“…Wang et al. found that the relative abundance of Lactobacillus was significantly reduced in POF patients and it is less abundant in postmenopausal women than in POF patients ( 23 ). Wu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the control group, the three highest relative expression dominant microbiomes were Lactobacillus, Muribaculaceae and Monoglobus. Lactobacillus plays an important role in maintaining human health and is considered as one of the most important probiotics in human intestinal [31]. It had been reported that Lactobacillus could inhibit the growth and reproduction of pathogenic bacteria [32].…”
Section: Discussionmentioning
confidence: 99%
“…In menacme and perimenopause, medium and short Gram-positive bacilli are more frequent, and in the event of dysbiosis, a polymicrobial population predominates. With menopause, there appears to be a reduction in lactobacilli associated with higher serum levels of folliclestimulating hormone (FSH) and lower estrogen levels (9). Intriguingly, more recently, researchers observed that in cases of postmenopausal women complaining of vaginal dryness and irritation, there is a significant frequency in the vagina of BVAB1, which morphologically presented as a curved Gram-negative bacillus, similar to Mobiluncus sp.…”
Section: Vaginal Microbiota and Menopausementioning
confidence: 99%